Intracellular self-assembly based multi-labeling of key viral components: Envelope, capsid and nucleic acids. (August 2016) - Wen, Li; Lin, Yi; Zhang, Zhi-Ling; Lu, Wen; Lv, Cheng; Chen, Zhi-Liang; Wang, Han-Zhong; Pang, Dai-Wen
Abstract: Envelope, capsid and nucleic acids are key viral components that are all involved in crucial events during virus infection. Thus simultaneous labeling of these key components is an indispensable prerequisite for monitoring comprehensive virus infection process and dissecting virus infection mechanism. Baculovirus was genetically tagged with biotin on its envelope protein GP64 and enhanced green fluorescent protein (EGFP) on its capsid protein VP39. Spodoptera frugiperda 9 (Sf9) cells were infected by the recombinant baculovirus and subsequently fed with streptavidin-conjugated quantum dots (SA-QDs) and cell-permeable nucleic acids dye SYTO 82. Just by genetic engineering and virus propagation, multi-labeling of envelope, capsid and nucleic acids was spontaneously accomplished during virus inherent self-assembly process, significantly simplifying the labeling process while maintaining virus infectivity. Intracellular dissociation and transportation of all the key viral components, which was barely reported previously, was real-time monitored based on the multi-labeling approach, offering opportunities for deeply understanding virus infection and developing anti-virus treatment.